Trust in Doctors, Positive Attitudes, and Vaccination Behavior: The Role of Doctor–Patient Communication in H1N1 Vaccination. Issue 11 (19th September 2022) - Borah, Porismita; Hwang, Juwon
ABSTRACT: Although there is a wide variety of scientific evidence that demonstrates the benefits of vaccination on a multitude of diseases, vaccination rates remain low while misperceptions about vaccines are on the rise. The primary objective of the present study is to examine the role of doctor–patient communication and vaccination. We test the impact of doctor–patient communication on trust in doctors' vaccine recommendations as a mediator, to understand the mechanisms leading to positive vaccination attitudes, and ultimately leading to actual H1N1 vaccination behavior. We use data from a nationally representative U.S. sample from one of the Multimedia Audience Research Systems (MARS) data sets collected by Kantar Media. Our results demonstrate the crucial role of doctor–patient communication in building patients' trust in doctors, which in turn positively impact vaccination attitudes and H1N1 vaccination behavior. Unlike other preventive health measures, getting vaccines after a pandemic is a critical decision because these vaccines are previously unknown. Our finding implies that verified communication from the physician's office may be one of the effective strategies during or after a pandemic. Our findings have implications for public health organizations to incorporate effective vaccination communication and could have critical implications for the COVID-19 vaccination.